2016
DOI: 10.3109/13880209.2015.1133659
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of intracellular expression of IFNγ and IL-2 in culture of splenic T lymphocytes by some flavonoid glycosides ofAlchornea floribunda

Abstract: Context Alchornea floribunda Mü ll. Arg. (Euphorbiaceae) leaves are widely used in ethnomedicine for the management of rheumatism, arthritis and toothache. Objective In this study, flavonoid glycosides isolated from Alchornea floribunda were screened for their effect on the intracellular expression of interferon-gamma (IFNg) and interleukin-2 (IL-2) type-1 cytokines. Materials and methods Chromatographic purification of the ethyl acetate fraction of the methanol leaf extract led to the isolation of seven flavo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…On the other hand, cytokine, a soluble extracellular protein or glycoprotein, is mainly produced from leukocytes (often lymphocyte) and possesses multiple targets and multiple functions such as modulating the development, differentiation, activation and function of immune cells, and engaging in innate and adaptive host defenses against inflammation. Recent studies have indicated that some CHMs influenced immune responses through modulation of mRNA transcript and protein expression of cytokines such as IL-2, IL-4, IL-6, IL-10, and IL-12 (Spelman et al, 2006;Ma et al, 2013;Okoye et al, 2016). Results of our study suggest that the CHMs supplements increased the concentration of both type-1 cytokine IL-2 and type-2 cytokine IL-6 in serum for late-lactation cows.…”
Section: Discussionsupporting
confidence: 55%
“…On the other hand, cytokine, a soluble extracellular protein or glycoprotein, is mainly produced from leukocytes (often lymphocyte) and possesses multiple targets and multiple functions such as modulating the development, differentiation, activation and function of immune cells, and engaging in innate and adaptive host defenses against inflammation. Recent studies have indicated that some CHMs influenced immune responses through modulation of mRNA transcript and protein expression of cytokines such as IL-2, IL-4, IL-6, IL-10, and IL-12 (Spelman et al, 2006;Ma et al, 2013;Okoye et al, 2016). Results of our study suggest that the CHMs supplements increased the concentration of both type-1 cytokine IL-2 and type-2 cytokine IL-6 in serum for late-lactation cows.…”
Section: Discussionsupporting
confidence: 55%